Staphylococcus aureus resistente à vancomicina: uma realidade clínica - Freitas, Cícero Carlos de; Rabello, Renata Fernandes; Freitas, Alexandre Gil de (Brazilian Journal of Sexually Transmitted Diseases, 1998)
Staphylococcus aureus represents a very serious clinicai concern, as it can rapidly develop resistance to almost ali new discovered antibiotics. Early, in 1940, all S. aureus infections were cured by penici/lin G; late, in 1950, however, almost 50% of them were resisrant to that beta-lacram, by penicillinase (a btta-lactamase enzyme) production. ln 1960, the synthesis of methicillin (a penicillinase-resistant btta lactam), togtther with the discovery of oral cephalosporins, suggested the eradication of t/ie penicillin•resistant staphylococcal infections. This was not so, however: by late 1970s, methicil/in-resistant Staphylococcus aureus (MRSA) strains tmerged a11d became increasingly more prevalent as nosocomial pathogens. Then, vancomycin (available since 1958) provided effective therapy for MRSA strains. Nevmheless, following lhe emergence of vancomycin-resistant strains of coagulase-negative staphylococci, we are already talking about a MRSA clinicai strain with resistance to vancomycin (VRSA) e MIC >8μgl mL). So, the complett cure of MRSA infections can not bt effective without the discovery of newer and more active antibiotics. Besides, we must develop a better antibiotictherapy, in order to preveni inducrion or selection of resistant or tolerant bacterial srrains. 0n the contrary, we will probably flow into the post-antibiotic era, maybt. more harmful than the preantibiotic one, when those strains had not still bten selecred.